Development and Validation of Comic-based Learning Module in Physics (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
Providing instructional materials that support the diverse learning styles and needs of 21st-century learners is becoming a trend in today's online learning. Thus, this descriptive developmental research design aimed to develop Comic-based Learning Modules (CLM) as instructional material envisioned to meet these learners' needs for a better understanding of Physics concepts. This study employed the ADDIE model for the instructional material development design. The initial developed CLM was revalidated following the comments and suggestions of the validators before distribution for online learning. Four experts validated the CLM in terms of content/lessons, illustrations, additional features, language, layout, and overall presentation using a researcher-made criterion-based reference evaluation tool. The validators rated the developed instructional material featuring three CLM as